Africa’s Image on American and Chinese Screens: Case Study of ‘Black Panther’ and ‘Operation Red Sea’ - Taling Tene Rodrigue (Department of Communications, Universitas Islam Indonesia, 2021)
In the wave of industrialization and internationalization of the Chinese Film Industry, the Chinese blockbuster ‘Operation Red Sea’ burst out as the 2018’s revelation in terms of quality standards and visual effects. The movie starred a Chinese navy team, ‘Jiaolong’, made of eight highly-trained and well-armed commandos to protect overseas Chinese nationals, rescue hostages, and handle a terrorist organization involved in nuclear weapons’ deals. However, Africa is featured as the film’s background story, and warfare actions’ playground, displaying to the domestic and world audience the old made-up clichés of Africa blended with war, terrorism, piracy and desert. Meanwhile, in the same year, Hollywood released ‘Black Panther’, a blockbuster which as well featured Africa as the film’s background story and actions’ playground, but that surprisingly overturned Hollywood’s century-old tradition of picturing a dark Africa full of political turmoil, wars, famine, diseases and illegal migrations. It also downplayed Marvel’s obsession with ‘White Super-heroism’. With regards to these paradigms shifts, the article, through a comparative study of the two hits mentioned above, aims at highlighting the media portrayal of Africa on American and Chinese screens, digging out the motives behind Hollywood upturn on Africa’s narrative, and identifying possible solutions for the Chinese Film Industry to improve its experience of ‘African thematic movies’ while avoiding Hollywood’s past mistakes. Keywords: Media portrayal of Africa, African thematic movies, Hollywood, Chinese film industry, Black Panther, Operation Red Sea.